Android Game HUPROSED (Human Reproductive System and Sex Education) as Learning Media on Human Reproductive System Topic - Putri Sekar Melati; Eka Cahya Prima; Eliyawati Eliyawati (Journal of Science Learning, 2023)
The topic of the Human Reproductive System integrated with comprehensive sex education was selected for this research because the concept of the human reproductive system is highly related to daily life. This study aims to develop an Android game application named "HUPROSED" for learning media on human reproductive system topics integrated with sex education. The DDD-E model used as the research method consists of deciding, designing, developing, and evaluating. The deciding stage begins with analyzing content and software. The designing stage consists of making a game hierarchy and storyboard. Then, the application was developed based on the previous stage. The last stage is evaluating, which involves three expert judges, three science teachers, and forty-six students chosen to review the application by purposive sampling. The total average results from the expert judgment show a score of 3.37. The results from teachers and students conduct a score of 3.23 and 3.25. It can be concluded that the development of the game "HUPROSED" using Unity 2019 is categorized as "good" for learning media on the human reproductive system topic.